Determinación de caudales máximos usando la curva de Intensidad Duración y Frecuencia en la Cuenca Santiago de Chuco. La Libertad. 2022 - Bermeo García, Kevin Anthony (2023)
In rainfall-runoff models, Intensity-Duration-Frequency curves (IDF Curves) are commonly used to determine the maximum design flows used in sizing hydraulic infrastructures and prevent flooding. For these reasons, the objective of the present work was to determine the maximum flows using the Intensity, Duration and Frequency curve, to achieve this, the delimitation, geomorphological and physiographic analysis of the basin was carried out, analysis of the maximum precipitation in 24 hours, and the maximum flows for 10, 25, 50, 100 and 200 years, through alternate blocks, the information was obtained from satellite images and national charts processed in ARCGIS, we obtained the DEM (Digital Terrain Model) to delimit the basin and obtain its geomorphological parameters, in addition, a probabilistic statistical analysis of the maximum precipitation data of 24 hours of a period of 39 years was developed (1981 to 2021), obtained from NASA, an analysis of doubtful data was made by the Water Resources Council method, and theoretical precipitation distribution functions (Weibull) and Normal probability, Log Normal of two Parameters, were applied. Gumbel, Pearson III, and Log Pearson III. for the frequency analysis, checking the goodness-of-fit test by the Kolmogorov – Simirnov method. The maximum rainfall for 24 hours was applied to the Dyck and Peschke model. The design storm that was used in the simulation of the precipitation - runoff relationship was defined for each of the stations. To determine the design storm, the alternating block method was used. The area of the basin was 1,410.78 km2, perimeter 170.8 km, maximum elevation 4,772.82 m, minimum elevation 1,682.87 m, average basin slope of 24.93%, and 57.60 km from the main river, length of the water network of 412.74 km. The precipitation data were fitted to the Pearson III and Log Pearson III distribution. The maximum design flow was determined for 10, 25, 50, 100, 140 and 200 years, obtaining 19.80; 86.90; 204.80; 414.40; 564.20 and 764.0 m3/s respectively.